Analisis Pasang Surut Perairan Pulau Pelapis, Kabupaten Kayong Utara - Maryani; Rizqan Khairan Munandar; Dayang Nur Eza Fatiha (Program Studi Ilmu Kelautan, FIPAK, Universitas OSO, 2024)
Pelapis Island is one of the islands located in Dusun Raya, Pelapis Village, District. Karimata Islands, Kab. North Kayong, Prov. West Kalimantan. The pelapis island consists of several other small islands, both inhabited and uninhabited. Pelapis village is a village that has a variety of potential natural beauty and abundant natural resources that can be enjoyed. Tides are one of the oceanographic parameters that have a big influence on waters. Tides are fluctuations in sea level due to the gravitational force of objects in the sky, especially the sun and moon, on the mass of sea water on earth. This research aims to analyze the characteristics of tides in the waters of Pelapis Island, North Kayong Regency. Analysis was carried out using a tide staff 350 cm long for 3 days every 1 hour for 24 hours. The results of the analysis show that the tidal pattern in the waters of Pelayang Island has a semi-diurnal tidal type or high and low tides that occur twice a day. From the observations we made in the waters of the Pelaway Island Water Pier, the lowest tide was at around 20.00 WIB, namely 61 cm and continued to rise slowly so that the highest peak tide occurred at 07.00-09.00 WIB at a height of 265 cm. Then sea water will experience a continuous decline. Factors that influence tidal characteristics in this region, such as astronomy, include the position of the moon and sun, as well as local meteorological conditions. In addition, this research also identifies the impact of climate change on tidal patterns, which can affect the ecosystem and economic activities of local communities.